2020
DOI: 10.1186/s12889-020-09331-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics and the epidemiology of tuberculosis in China from 2004 to 2017 by the nationwide surveillance system

Abstract: Background China has always been one of the countries with the most serious Tuberculosis epidemic in the world. Our study was to observe the Spatial-temporal characteristics and the epidemiology of Tuberculosis in China from 2004 to 2017 with Joinpoint regression analysis, Seasonal Autoregressive integrated moving average (SARIMA) model, geographic cluster, and multivariate time series model. Methods The data of TB from January 2004 to December 2017 were obtained from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…It could help to find meaningful turning points or trends in disease incidence and mortality over time. To the best of our knowledge, few studies have described TB incidence and mortality temporal variations in China using this model [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It could help to find meaningful turning points or trends in disease incidence and mortality over time. To the best of our knowledge, few studies have described TB incidence and mortality temporal variations in China using this model [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium tuberculosis (Mtb) is a highly survivable intracellular bacterium that causes tuberculosis (TB), which infects about one-third of the world's population and poses a major threat to human health [ 1 ]. Because of its large population base, China has a high incidence of TB, second only to India in terms of the total number of cases [ 2 ]. Studies have shown [ 3 ] that the prevalence of pulmonary tuberculosis (PTB) in China differs greatly between eastern and western regions, with the prevalence in western regions significantly higher than in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…China has always been one of the countries with the most serious TB epidemic all over the world. In 2017, about 60.08/100'000 cases of TB were reported in China (15). In addition, skin test positivity ranged from 15% to 42%, and IGRA positivity rate ranged from 13% to 20% in rural China (16).…”
Section: Occurrence Of Tuberculosis Infection In Patients With Igg4-rdmentioning
confidence: 99%